2014
DOI: 10.1007/s10534-014-9779-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactoferrin on intestinal epithelial cell growth and differentiation: an in vivo and in vitro study

Abstract: This study was designed to analyse the effects of human (h) and bovine lactoferrin (bLF) on the growth and differentiation of intestinal cells using the mice model supplemented with Lactoferrin (LF) and the enterocyte-like model of Caco-2 cells which spontaneously differentiate after confluency. In mice, bLF supplementation increased jejunal villus height and the expression of several intestinal brush border membrane enzymes activities. Addition of bLF or hLF to undifferentiated Caco-2 cells was able to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…In view of the viability of attached cells to the ordered collagen membrane, the transcript expression of markers associated with IECs by qRT‐PCR was examined (Blais et al, ). At 8 DOC we found that cultured primary and frozen/thawed cells maintained a significant expression of maltase and alkaline phosphatase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the viability of attached cells to the ordered collagen membrane, the transcript expression of markers associated with IECs by qRT‐PCR was examined (Blais et al, ). At 8 DOC we found that cultured primary and frozen/thawed cells maintained a significant expression of maltase and alkaline phosphatase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the effect of hLF on cellular proliferation is controversial. The reason for the conflicting effect of hLF is not clear, but the effect of hLF on the cell growth appeared to be dependent on the cell types, doses used to test, and both the endogenous and exogenous co-stimulating or co-inhibiting factors in the cells and culture medium [24]. Additionally, the preparation method and the status of hLF could be another possible reason [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LF showed a growth-inhibitory effect on some cell types [20][21][22][23]. Therefore, the inconsistent effects of LF on cell growth presumably depend on cell types, the doses used, and possibly the presence of co-growth-promoting or co-growth-inhibiting factors or signals [11,24].…”
Section: Introductionmentioning
confidence: 99%
“…These health benefits include a variety of LF protective effects, ranging from antimicrobial and anti‐inflammatory properties to stimulation of proliferation and differentiation (reviewed in Ref. ) and antiapoptotic effects . However, little is known about the extent to which these properties of LF contribute to stabilization of intestinal epithelial barrier function.…”
Section: Introductionmentioning
confidence: 99%